2021
DOI: 10.25015/17202134152
|View full text |Cite
|
Sign up to set email alerts
|

Faktor-Faktor yang Mempengaruhi Adopsi Inovasi SITT Sapi Potong di Kabupaten Bengkulu Selatan

Abstract: Adoption of the crop-livestock system (CLS) technology innovation is influenced by internal and external factors of farmers. The purpose of this study was to determine the influencing factors of CLS adoption technology innovation for beef cattle in South Bengkulu Regency. The research was carried out from January to April 2020 at the location of the Integrated intensive livestock village (Integrated ILV) in South Bengkulu Regency located at 5 villages. Data were collected through a census involving 73 farmers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…With the ability to identify these problems, farmers will also be able to find out what innovation needs are needed to solve them. Harta [9] said that the ability of farmers to adopt innovations affected by the attitude of farmers towards the innovations offered because attitudes will be able to change the farmer's perspective on the innovations introduced. Likewise, Muhyidin [10] opinion revealed that one factor that determines whether the leading actors adopt innovation is the farmers' attitude (see figure 4).…”
Section: Beef Cattle Farming Business Innovation Transfer Modelmentioning
confidence: 99%
“…With the ability to identify these problems, farmers will also be able to find out what innovation needs are needed to solve them. Harta [9] said that the ability of farmers to adopt innovations affected by the attitude of farmers towards the innovations offered because attitudes will be able to change the farmer's perspective on the innovations introduced. Likewise, Muhyidin [10] opinion revealed that one factor that determines whether the leading actors adopt innovation is the farmers' attitude (see figure 4).…”
Section: Beef Cattle Farming Business Innovation Transfer Modelmentioning
confidence: 99%